Bortezomib, thalidomide, and dexamethasone with or without daratumumab for transplantation-eligible patients with newly diagnosed multiple myeloma (CASSIOPEIA): health-related quality of life outcomes of a randomised, open-label, phase 3 trial. Issue 12 (December 2020) - Roussel, Murielle; Moreau, Philippe; Hebraud, Benjamin; Laribi, Kamel; Jaccard, Arnaud; Dib, Mamoun; Slama, Borhane; Dorvaux, Véronique; Royer, Bruno; Frenzel, Laurent; Zweegman, Sonja; Klein, Saskia K; et al.
Summary: Background: In part 1 of the two-part CASSIOPEIA study, treatment before and after autologous haematopoietic stem-cell transplantation (HSCT) with daratumumab plus bortezomib, thalidomide, and dexamethasone (D-VTd) significantly improved rates of stringent complete response and progression-free survival versus bortezomib, thalidomide, and dexamethasone (VTd) in patients with newly diagnosed multiple myeloma. Methods: CASSIOPEIA is an ongoing randomised, open-label, active-controlled, parallel-group, phase 3 trial done at 111 academic and community practice centres in Europe. Transplantation-eligible adults with newly diagnosed multiple myeloma were randomly assigned (1:1) to D-VTd or VTd. Treatment consisted of four 28-day cycles of induction therapy before autologous HSCT and two 28-day cycles of consolidation therapy after. In this prespecified secondary analysis, patient-reported outcomes were assessed using the European Organization for Research and Treatment of Cancer quality of life questionnaire-core 30-item (EORTC QLQ-C30) and EuroQol 5-dimensional descriptive system (EQ-5D-5L) questionnaire at baseline, after induction (cycle 4, day 28), and after consolidation (day 100 after autologous HSCT). The analysis was done in all patients in the intention-to-treat population with a baseline and at least one post-baseline patient-reported outcome assessment. The trial is registered at ClinicalTrials.gov (NCT02541383 ). Findings: Between Sept 22, 2015, and Aug 1, 2017, 1085 patients were enrolled and randomly assigned D-VTd (n=543) or VTd (n=542). Questionnaire completion rates were high at baseline (511 [94%] of 543 in the D-VTd group vs 510 [94%] of 542 in the VTd group). Compliance rates (calculated from the number of completed surveys as a proportion of the predicted number of participants still on study treatment) were high at post-induction (431 [84%] of 513 vs 405 [80%] of 509) and post-consolidation (414 [90%] of 460 vs 386 [88%] of 438) assessments and were similar between treatment groups. Mean changes in global health status scores from baseline to post-induction were not different between the D-VTd group (3·8 [95% CI 1·6 to 6·0]) and VTd group (2·9 [0·7 to 5·1]; p=0·43), or from baseline to post-consolidation between the two groups (D-VTd group, 9·7 (95% CI 7·4 to 11·9) vs VTd group, 8·7 (6·5 to 11·0; p=0·45). Improvements from baseline in EORTC QLQ-C30 global health status and EQ-5D-5L visual analogue scale scores were observed in post-consolidation scores in both groups. Post-consolidation scores showed significantly greater mean decreases in pain (−23·3 [95% CI −26·6 to −20·0] in the D-VTd group vs −19·7 [−23·0 to −16·3] in the VTd group; p=0·042), significantly smaller reductions in cognitive functioning (−5·0 [−7·6 to −2·4] vs −7·9 [−10·6 to −5·3]; p=0·036), and significantly greater improvements in emotional functioning (13·0 [10·4 to 15·5] vs 9·5 [6·9 to 12·1]; p=0·013) and in constipation (–3·2 [–7·3 to 0·9] vs 1·8 [–2·4 to 6·0]; p=0·025) with D-VTd versus VTd. Between-group differences in change from baseline for all other scales were not significant. Interpretation: D-VTd and VTd were associated with on-treatment health-related quality of life improvements from baseline in transplantation-eligible patients with newly diagnosed multiple myeloma. The significantly greater reductions in pain, less deterioration of cognitive functioning, and greater emotional functioning improvements complement the clinical benefits observed with D-VTd versus VTd, and support the addition of daratumumab to standard regimens in patients with newly diagnosed multiple myeloma. Funding: Intergroupe Francophone du Myélome, The Dutch-Belgian Cooperative Trial Group for Hematology Oncology, and Janssen Research and Development.